2016
DOI: 10.1177/1757913915626193
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful activities for improving the wellbeing of people with dementia: beyond mere pleasure to meeting fundamental psychological needs

Abstract: Aims: Dementia is being increasingly recognised as a major public health issue for our ageing populations. A critical aspect of supporting people with dementia is facilitating their participation in meaningful activities. However, research to date has not drawn on theories of ageing from developmental psychology that would help undergird the importance of such meaningful activity. For the first time, we connect existing activity provision for people with dementia with developmental psychology theories of agein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 72 publications
(77 reference statements)
0
57
0
Order By: Relevance
“…Activities are made meaningful through feelings of enjoyment and pleasure (Eakman, , ; Eakman, Carlson, & Clark, ; Kuosa et al, ; Vernooij‐Dassen, ). Enjoyment can be experienced during activity participation (Nyman & Szymczynska, ; Roland & Chappell, ), when looking forward to an activity (Roland & Chappell, ) or enjoyment of the outcome of an activity (Bishop & Purcell, ). Activities may be enjoyed for various reasons such as being a hobby (Bishop & Purcell, ), a means of relaxation (Bishop & Purcell, ; Han et al, ) or a connection to personal identity (Carless, ; Han et al, ; Milte et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activities are made meaningful through feelings of enjoyment and pleasure (Eakman, , ; Eakman, Carlson, & Clark, ; Kuosa et al, ; Vernooij‐Dassen, ). Enjoyment can be experienced during activity participation (Nyman & Szymczynska, ; Roland & Chappell, ), when looking forward to an activity (Roland & Chappell, ) or enjoyment of the outcome of an activity (Bishop & Purcell, ). Activities may be enjoyed for various reasons such as being a hobby (Bishop & Purcell, ), a means of relaxation (Bishop & Purcell, ; Han et al, ) or a connection to personal identity (Carless, ; Han et al, ; Milte et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…A person with declining abilities may seem reluctant to participate in an activity that was previously meaningful to them (Harmer & Orrell, ). However, adapting an activity or providing support to suit current needs and abilities can ease fears of failure and enable the person to cope with their health‐related losses while continuing to find meaning in the activity (Harmer & Orrell, ; Nyman & Szymczynska, ).…”
Section: Resultsmentioning
confidence: 99%
“…Implications for policy and practice PWD are to be encouraged and facilitated to participate in appropriate forms of physical activity as part of a public health strategy and for PWD to continue to enjoy quality of life (Bowes et al, 2013;Ginis et al, 2017;Nyman & Szymczynska, 2016). Similar to a previous systematic review of qualitative studies conducted with people with physical impairments and mobility limitations (Williams, Ma, & Martin Ginis, 2017), we found that a combination of goal (goal setting (behaviour)), support (social support (unspecified)), and communication (using a credible source) strategies would be promising for promotion of physical activity among PWD.…”
Section: Limitations and Ideas For Future Researchmentioning
confidence: 99%
“…[4] Although not every activity will appeal to every older person nor should the older person be engaged in a stimulating activity all the time, there is a need to facilitate participation in meaningful activities. [11] Persons living with dementia often lack opportunities especially with daytime activities and social companionship. [12] Han et al completed a synthesis of 34 qualitative studies.…”
Section: Meaningful Activitiesmentioning
confidence: 99%